Centre/ing decolonial feminist psychology in Africa. (September 2018) - Kessi, Shose; Boonzaier, Floretta
Psychology as a discipline has historically served the interests of dominant groups in society. By contrast, contemporary trends in psychological work have emerged as a direct result of the impact of violent histories of slavery, genocide and colonisation. Hence, we propose that psychology, particularly in its social forms, as a discipline centred on the relationship between mind and society, is well placed to produce the critical knowledge and tools for imagining and promoting just and equitable social relationships and social structures. Starting with an overview of the historical assumptions of the discipline that served to legitimate systems of slavery, colonisation and apartheid, this article then introduces a framework for centring decolonial, feminist ways of doing psychological work with a focus on the particularities of the African context. We argue that a decolonial feminist approach to psychology curricula and psychological research is necessary for the discipline to remain relevant in contemporary African contexts.